## Expanding (2a-7)(2a-7)

This expression represents the product of two identical binomials: **(2a-7)**. To find the answer, we can use the **FOIL** method, which stands for **First, Outer, Inner, Last**.

**Here's how it works:**

**First:**Multiply the first terms of each binomial: (2a) * (2a) =**4a²****Outer:**Multiply the outer terms of the binomials: (2a) * (-7) =**-14a****Inner:**Multiply the inner terms of the binomials: (-7) * (2a) =**-14a****Last:**Multiply the last terms of each binomial: (-7) * (-7) =**49**

Now, combine the results and simplify:

4a² - 14a - 14a + 49 = **4a² - 28a + 49**

Therefore, the expanded form of (2a-7)(2a-7) is **4a² - 28a + 49**.

**Note:** This expression is also known as the **square of a binomial**. The general formula for squaring a binomial is:

**(a + b)² = a² + 2ab + b²**

In this case, a = 2a and b = -7. You can use this formula to verify our answer.